Hospitality Students’ Perception About The Use of AI in Learning English at The Tourism Department of The Kupang State Polytechnic - Malelak, Merlin Luisa; Nazar, Asbi; L.F.Conterius, Agustino (Jurnal Manajemen Pelayanan Hotel, 2024)
The title of this study is Hospitality Students' Perceptions of the Use of AI in English Language Learning at the Tourism Department of Kupang State Polytechnic. This study aims to determine the perceptions of hospitality students about the use of artificial intelligence (AI) in English language learning, as well as the impact of the use of AI. Student perceptions are divided into 2, namely positive and negative. Some of them think that the use of AI is very helpful for them in understanding and mastering 4 basic English skills, namely reading, listening, writing and speaking and can improve their learning experience through a more personal and adaptive approach, which allows them to learn according to their respective needs. There are also students who have negative opinions regarding the use of AI in the English language learning process. They feel that with the AI application, students will be more dependent on the application and no longer read existing modules or books related to their respective fields of science in this case related to the hospitality industry. They may also trust the application more than the lecturer/teacher who teaches. According to them, this needs to be addressed more carefully and thoroughly so as not to harm other parties, especially teaching staff or practitioners who are experts in the field of science, especially English. The impact of using AI is also divided into two, namely positive and negative. The positive impact is that AI can improve the quality of English learning, help them know which parts need to be improved and speed up the learning process. AI also allows learning that can be accessed anytime and anywhere or study everywhere, students are ready for the world of work because they believe that increasing English skills will better prepare them to face the challenges of the world of work, especially in the tourism industry in this case the increasingly global hospitality. The negative impact according to students is that this application can create dependence on technology so that they no longer learn independently and think logically/critically. Students will also interact less with fellow students and teachers because AI reduces the opportunity to practice language in real social interactions. Despite everything, AI applications actually bring new breakthroughs in the world of technology and various related fields, especially 1 https://mapindo.ejurnal.info/index.php/manajemen_pelayanan_hotel Vol. x, No.x; year education. This application can actually support learning. The use of AI applications appropriately can accelerate the education process.